Influence of Structural Shape on Earth Pressure for High-Filled Cut-and-Cover Tunnel with and without Load Reduction Based on Discrete Element Method - Sheng Li; Liangliang Zhao; I-Hsuan Ho; Guixia Ning; Bentian Yu; Changdan Wang (Advances in Civil Engineering)
In the construction of the Loess Plateau in China, high-filled cut-and-cover tunnels (HFCCTs) had solved the problem of the shortage of land resources. However, this type of structure has a large amount of backfill soil, which leads to the problems of ultrahigh earth pressure and safety of the cut-and-cover tunnels (CCTs) lining structure. Previous studies have focused on the load reduction of various flexible materials, ignoring the influence produced by the shape of the CCT structure on the load reduction. Therefore, via a discrete element software, we investigated the changes of vertical earth pressure (VEP), vertical displacement, lateral earth pressure (LEP), and load transfer mechanisms around a HFCCT with consideration to two cases: (1) different shape of CCT structure; (2) the coupling of load reduction using expanded polystyrene (EPS) and the modified shape of the CCT lining structure. The results obtained by the discrete element method (DEM) revealed that an appropriate structural shape influenced the reduction of the VEP above the CCT and that the coupled effects of the load reduction using the EPS and shape modifications of the CCT lining structure could significantly reduce the VEP above the CCT, which enhanced the safety of the CCT. Meanwhile, the optimal values for the shapes of CCTs are derived.